FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2019-2021 - Amin Wijoyo; Nastasya Cindy Hidajat (Jurnal Bina Akuntansi, 2023)
The purpose of this study is to test and analyze how strong the influence of the independent variables leverage, corporate strategy, cash holding, and profitability both individually and simultaneously in influencing earnings management. The population that will be used in this study are manufacturing companies listed on the IDX for 2019 - 2021. The sample was determined using a purposive sampling technique and obtained a sample of 72 companies from 204 companies. The results of this study show that all independent variables simultaneously affect the dependent variable used in this study. Individually cash holding and profitability affect earnings management significantly, then leverage and corporate strategy do not significantly affect earnings management.